Election watchdogs transparency, accountability and integrity - Norris, Pippa 1953-; Nai, Alessandro 1981- (Oxford University Press, 2017)
"Recent years have seen resurgent interest in the potential capacity of transparency - the public availability of information - to improve democratic governance. Timely, accurate, granular and freely-available information is generally regarded as intrinsically valuable, as well as having many instrumental benefits. In development, transparency and accountability is generally thought to help plug the leaky pipes of corruption and inefficiency, channel public spending more efficiently, and produce better services. In the field of electoral governance, openness about the rules and procedures, outcomes, and decisions processes used by electoral authorities is widely assumed to build public trust, improve policy-making, and facilitate accountability. In the age of WikiLeaks, Twitter and Google, open governance, expanding information and communication, often seems like an unqualified good. Nevertheless, beyond popular buzzword sloganeering, evidence suggests that the impact of transparency on the quality of governance and elections remains mixed. Transparency also has a dark side, threatening trust, privacy, and security. To understand these issues more fully, this book seeks to assess the contemporary drive towards open electoral governance and to identify several conditions predicted to determine the success of transparency policies in strengthening electoral integrity. Chapters look at transparency in electoral governance at the international and state levels, as well as within civil society"...